2002
DOI: 10.1002/jcb.10354
|View full text |Cite
|
Sign up to set email alerts
|

Retinal neuroprotection by growth factors: A mechanistic perspective

Abstract: For more than a decade it has been known that certain growth factors inhibit apoptosis in genetically determined and experimental models of inner and outer retinal degeneration. The molecular mechanisms underlying these protective effects and the signaling that supports the survival of photoreceptors and retinal ganglion cells in these models have recently come under more in depth investigation. This paper reviews our current understanding of the balance of pro- and antiapoptotic signals that determine cell fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 129 publications
2
57
0
3
Order By: Relevance
“…Treatment with BDNF alone (without a graft) had no effect on the response latency which suggests that BDNF acts synergistically with other 'factors' released by the transplanted tissue. This combined effect may result in some restoration of the disturbed neural circuitry of the degenerating host retina which is supported by data from other investigators demonstrating neuro-protective effects of BDNF (Chaum, 2003;Ikeda et al, 2003;Keegan et al, 2003;Lawrence et al, 2004;Nakazawa et al, 2002;Paskowitz et al, 2004).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Treatment with BDNF alone (without a graft) had no effect on the response latency which suggests that BDNF acts synergistically with other 'factors' released by the transplanted tissue. This combined effect may result in some restoration of the disturbed neural circuitry of the degenerating host retina which is supported by data from other investigators demonstrating neuro-protective effects of BDNF (Chaum, 2003;Ikeda et al, 2003;Keegan et al, 2003;Lawrence et al, 2004;Nakazawa et al, 2002;Paskowitz et al, 2004).…”
Section: Discussionmentioning
confidence: 53%
“…These studies have also provided investigators with information to assist in optimizing therapeutic strategies aimed at preventing visual loss and or restoring lost vision. Therapeutic interventions in animal models, including growth factor treatment, gene therapy, retinal prosthetics and retinal cell transplantation, have been presumed to improve visual sensitivity Seiler, 2002, 2004;Chaum, 2003;Delyfer et al, 2004;Loewenstein et al, 2004;Lund et al, 2001) by delaying the progression of the disease and/or by rescuing the remaining host photoreceptors. Some studies of retinal sheet transplants have suggested that transplanted photoreceptors may also contribute directly to the visual restoration Seiler et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotrophic factors have the ability to modulate neuronal growth during development to maintain existing cells and to allow recovery of injured neuronal populations. 68 In the retina, Lavail et al 69 More recently, recombinant AAV-2/2 encoding fibroblast growth factor family members FGF-2, FGF-5 and FGF-18 have been evaluated using a transgenic rat model of retinitis pigmentosa, the S334ter-4 rat line that expresses a mutated rhodopsin gene. Despite the lack of significantly increased electroretinograms (ERGs), treated rats displayed a greater number of surviving photoreceptors following subretinal injection of these vectors, suggesting the ability of these factors to protect photoreceptors from apoptosis in this rat model of RP.…”
Section: Gene Transfer In Animal Models Of Retinal Degenerationmentioning
confidence: 99%
“…The hydrogels employed (i.e., poly(ethylene glycol)-poly(lactic acid) (PEGPLA)) are composed of polymer elements that have been shown to dramatically increase biocompatibility of implanted devices [18], potentially reducing scar formation at the implant site. Additionally, these hydrogels can be designed to release a variety of bioactive compounds including neurotrophins, which are biomolecules that can influence neuronal survival and neurite extension in the retina [19][20][21]. Neurotrophins should promote growth of neuronal extensions toward the array, and thus decrease electrode-target separation distance and therefore thresholds.…”
Section: Introductionmentioning
confidence: 99%